The Lost House - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Lost House" by Richard Harding Davis is a novel likely written in the late 19th century. The narrative follows Austin Ford, a young journalist who becomes embroiled in a tense situation after he discovers a note claiming that a woman named Dosia Pearsall Dale is being held against her will and is in imminent danger. Along with the Second Secretary at the American Embassy, Ford dives into a mystery that leads him into the dark side of London society as he attempts to uncover the truth and rescue the woman in peril. At the start of the story, we find an unoccupied American Embassy during a dull day in London, with various diplomats away on obligations. The remaining Second Secretary receives a mysterious note wrapped around a half-crown, which reveals that Dosia Pearsall Dale is trapped in a house and her life is in danger. The note prompts Ford, full of excitement and urgency, to investigate the message, eventually leading him to the area of Sowell Street where he believes she is being held. Ford$1 (Bs determination to solve the mystery is evident as he navigates police dismissals and challenges, and his character quickly transforms from a bored observer to an active participant in what appears to be a race against time to save the young woman from her dangerous uncle and an ominous doctor, Dr. Prothero. (This is an automatically generated summary.)s
Release date is 1999-07-01
Produced by Aaron Cannon, and David Widger
Keywords: Ambassadors -- England -- Fiction